Prenatal diagnosis of a distal 3p deletion associated with fetoplacental chromosomal discrepancy and confined placental mosaicism detected by array comparative genomic hybridization - Chih-Ping Chen; Yi-Yung Chen; Schu-Rern Chern; Peih-Shan Wu; Jun-Wei Su; Wen-Lin Chen; Wayseen Wang (Elsevier, 2013)
Objective: This study is aimed at prenatal diagnosis of a distal 3p deletion associated with fetoplacental chromosomal discrepancy and confined placental mosaicism, and providing evidence for the limitation of array comparative genomic hybridization (aCGH) on placental tissues for molecular cytogenetic characterization of prenatally detected aneuploidy. Case Report: A 30-year-old woman underwent amniocentesis at 18 weeks of gestation because of maternal anxiety. Results of amniocentesis revealed a distal deletion of chromosome 3p. A malformed female fetus was delivered at 20 weeks of gestation with brachycephaly and facial dysmorphisms, and a cytogenetic analysis of the cord blood revealed a karyotype of 46,XX,del(3)(p26.1),inv(9)(p12q13). A whole-genome aCGH on uncultured cord blood and placental tissue was performed. The aCGH on cord blood revealed a 7.4-Mb deletion at 3p26.3-p26.1. However, the aCGH on placental tissue revealed a 32.42-Mb gene dosage increase at 3p26.1-p22.1 and a 26.28-Mb gene dosage increase at 1p36.33-p36.11 in addition to a 7.4-Mb deletion at 3p26.3-p26.1, indicating confined placental mosaicism for partial trisomy 3p (3p26.1→p22.1) and mosaicism for partial trisomy 1p (1p36.33→p36.11). The 7.4-Mb deleted region of 3p26.3-p26.1 contained the following genes: CHL1, CNTN4, CRBN, LRRN1, and ITPR1. Conclusion: Fetal tissue and amniocytes offer more reliable resources for aCGH characterization of prenatally detected aneuploidy compared with placental tissues. A molecular cytogenetic evaluation of prenatally detected aneuploidy using placental tissue should raise concerns of confined placental mosaicism and fetoplacental chromosomal discrepancy.